A thiol-functionalized zirconium metal–organic cage for the effective removal of Hg2+ from aqueous solution. (24th November 2020) - Qi, Xiang-Juan; Sun, Min; Hou, Bao-Shan; Yu, Xiang; Shan, Guo-Gang; Sun, Chun-Yi; Yousaf, Afifa; Wang, Xin-Long; Su, Zhong-Min
Abstract: The mercury ions in waste water have threatened public health and environmental protection. In this sense, novel materials with outstanding performances for removal of Hg 2+ are imperative. Herein, we demonstrate a thiol-functionalized zirconium metal–organic cage (MOC-(SH)2 ) with excellent dispersion displays ideal properties for Hg 2+ capture. MOC-(SH)2 exhibits the ability of removing Hg 2+ in aqueous solutions with a capacity of 335.9 mgHg2+ /gMOC-(SH)2, which surpasses that of classical Zr-based metal–organic framework Uio-66-(SH)2 by 1.89 folds. The higher loading capacity of MOC-(SH)2 is probably owing to the excellent dispersion of the discrete cage, which makes the accessibility of binding sites (thiol) easier. Additionally, 99.6% of Hg 2+ can be effectively captured by MOC-(SH)2 with the concentration decreased from 5 to 0.02 ppm reaching the permissible limit for Hg 2+, outperforming the performance of Uio-66-(SH)2 . The excellent absorption property of MOC-(SH)2 is also achieved in terms of superior selectivity under the presence of competitive metal ions. Meanwhile, the regenerated MOC-(SH)2 can be reused without apparent loss of Hg 2+ loading capacity. UV–vis absorption spectra, IR spectra and emission spectra further verified the strong chemical affinity between Hg 2+ and the thiol of MOC-(SH)2 . The study lays the groundwork for using Zr-MOCs in the removal of toxic metal ions and environmental sustainability.